Migration and Integration Research Filling in Penninx's Heuristic Model - Garcés-Mascareñas, Blanca; van Heelsum, Anja (IMISCOE, 2013)
Rinus Penninx's groundbreaking work has helped to systematise and classify existing research in the field of migration and ethnic studies. His heuristic model makes an important distinction between immigration and integration research and, within the latter, between socio-economic, ethno-cultural and legal-political dimensions. Written as a tribute to Penninx, this volume consists of contributions by 15 of his former PhD students covering all the main categories of his heuristic model.